2022
DOI: 10.1071/an20418
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of narasin intake affects ruminal metabolism and growth of lambs

Abstract: Context Ionophores improve rumen fermentation efficiency, average daily gain (ADG) and feed efficiency. However, the effects of providing ionophores to grazing animals are extremely variable, primarily due to infrequent supplement intake. Aim This study aimed to evaluate the effect of frequency of narasin intake on ruminal fermentation, nutrient digestibility and growth of lambs. Methods In Experiment I (metabolism assay), four rumen-cannulated wethers (1/2 Dorper × 1/2 Santa Inês) were assigned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…There is no consensus in the literature on the effects of narasin on ruminal SCFA concentration. In diets with high forage content, the inclusion of ionophore increased the total SCFA concentration ( Oliveira et al, 2022 ; Polizel et al, 2020 ), while in diets with high concentrates, the total SCFA concentration decreases ( Polizel et al, 2021 ). In agreement with the results reported by Pasqualino et al (2020) , the present study demonstrated that there is no residual effect of narasin on the SCFA concentration in the rumen fluid after the removal of the ionophore.…”
Section: Discussionmentioning
confidence: 99%
“…There is no consensus in the literature on the effects of narasin on ruminal SCFA concentration. In diets with high forage content, the inclusion of ionophore increased the total SCFA concentration ( Oliveira et al, 2022 ; Polizel et al, 2020 ), while in diets with high concentrates, the total SCFA concentration decreases ( Polizel et al, 2021 ). In agreement with the results reported by Pasqualino et al (2020) , the present study demonstrated that there is no residual effect of narasin on the SCFA concentration in the rumen fluid after the removal of the ionophore.…”
Section: Discussionmentioning
confidence: 99%